2015
DOI: 10.5120/19594-1383
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Various Attacks on MANET

Abstract: Mobile Ad hoc Networks (MANET) is a part of wireless networks. No wires and fixed routers are used in this type of network. It is not everlasting network; it is the short term network. Nodes has the capability to self organize themselves and it follows infrastructure less architecture. Network is formed by number of nodes moving in an inconsistent manner. They do not form any topology. Few examples of Ad hoc wireless network devices are Laptops, palmtops, smart phones etc [6]. And every nodes further acts as r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…In paper [13], MANET is an important aspect of any wireless networks. No ropes and immovable routers are used in these kinds of network.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In paper [13], MANET is an important aspect of any wireless networks. No ropes and immovable routers are used in these kinds of network.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The simulation result has shown that there is difference performance in throughput when there is an attack. Feng, Li, Chen, and Tang [7] projected a way for defencing against multi-source Sybil attacks in VANET. During this paper, author propose an occasion based name system (EBRS), throughout that dynamic name and trustworthy price for each event are used to suppress the unfold of false messages.…”
Section: Related Workmentioning
confidence: 99%
“…Black hole attack: In this type of attack all the packets are dropped by the malicious node and fake packets are further send [4].…”
Section: Securitymentioning
confidence: 99%
“…As soon as a node becomes malicious node it hampers the communication. So there is need of secure routing and secure routing protocol that can provide security against the malicious behavior of nodes [4].…”
Section: Securitymentioning
confidence: 99%
See 1 more Smart Citation